2017
DOI: 10.1002/mop.30615
|View full text |Cite
|
Sign up to set email alerts
|

A compact sixteenth‐mode substrate integrated waveguide bandpass filter with improved out‐of‐band performance

Abstract: This article presents a compact sixteenth‐mode substrate integrated waveguide (SMSIW) bandpass filter operating at fundamental mode TM01. The filter size is reduced by introducing SMSIW circular cavity. It occupies only 6.25% of the conventional substrate integrated waveguide (SIW) circular cavity with same resonant frequency. The higher‐order mode TM02 of the circular cavity is suppressed by etching two slots on the ground plane to improve out‐of‐band performance. Measured results show that an out‐of‐band rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The authors of [82] reported a compact and dual-pole bandpass filter using SMSIW cavity resonators. Each SMSIW cavity resonator excites the fundamental TM 01 mode.…”
Section: H Sixteenth-mode Siw (Smsiw)mentioning
confidence: 99%
“…The authors of [82] reported a compact and dual-pole bandpass filter using SMSIW cavity resonators. Each SMSIW cavity resonator excites the fundamental TM 01 mode.…”
Section: H Sixteenth-mode Siw (Smsiw)mentioning
confidence: 99%
“…Several attempts have been made to reduce the size of SIWs while maintaining or even enhancing the performance. Various RF applications have been realized, such as half-mode SIWs (HMSIWs) [ 10 , 11 ], quarter-mode SIWs (QMSIWs) [ 12 , 13 ], eight-mode SIWs (EMSIWs) [ 14 , 15 ], sixteen-mode SIWs [ 16 ], and ridged quarter-mode SIWs [ 17 ]. According to image theory, in-phase fields exist on opposite sides; thus, the symmetric plane of an SIW is cut into two halves to obtain an HMSIW [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these structures do not exhibit wide‐stopband performance. Recently, a compact sixteenth‐mode SIW (SMSIW) cavity is proposed, and the size of the cavity is reduced by 93.75% compared with the standard SIW circular cavity . The proposed SMSIW cavities are used to design bandpass filters, and they exhibit simple geometrical configuration, compact size, low loss, and ease of fabrication.…”
Section: Introductionmentioning
confidence: 99%